Mídia virtual e a diáspora brasileira : a identidade nacional retratada em sites para expatriados - Chaves, Carolina Wiedemann (2012)
The present research aims to point out identity markers which built up the national imaginative idea of Brazilian expatriates in internet sites for such communities around the world. The corpus of analysis was constructed from a selection of thirteen sites of Brazilian communities, chosen from a selection of such sites in a list presented by the Ministry of Foreign Affairs of Brazil in its site. The theoretical part studies and explores the concepts of identity, cultural and national identity, imagination, Brazilian national identity, globalization, expatriation, and virtual communication. Discourse analysis was used to survey and understand the items which build up the identity of a Brazilian person living abroad. As points of identification and perpetuation of Brazilian national identity for such Brazilian expatriates, the main issues identified were: the use of green and yellow as colors identifying Brazil, the presence of Brazilian rhythms as Samba, Axé, Forró, batucada, among others, the enhancement of friendliness and joy, the Brazilian-Portuguese language.